2011
DOI: 10.5006/1.3659504
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically Influenced Corrosion in UNS S31653: Detection and Analysis Using Electrochemical Noise Technique

Abstract: Austenitic stainless steels are susceptible to microbiologically influenced corrosion (MIC), and biofilms of slime-forming bacteria can affect the integrity of the passive film of the stainless steel components. An attempt was made to detect and analyze the MIC on UNS S31653 using electrochemical noise (EN) technique. The progress of MIC was monitored in natural reservoir water, concentrated with biofilm-forming microbes along with 0.5 M sodium chloride (NaCl) and nutrients, as well as in a similar media min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…SRB may propagate quickly in the locally anaerobic environment beneath the iron rich tubercles produced by IOB [24]. The interaction between SRB and IOB could accelerate the pitting corrosion process of carbon steel [25].…”
Section: Introductionmentioning
confidence: 99%
“…SRB may propagate quickly in the locally anaerobic environment beneath the iron rich tubercles produced by IOB [24]. The interaction between SRB and IOB could accelerate the pitting corrosion process of carbon steel [25].…”
Section: Introductionmentioning
confidence: 99%
“…EPN transients are typically characterized by a relatively fast rise and slow (e.g., exponential) decay of the absolute value of the EPN signal. 6,8,[10][11]23,[48][49][50][63][64]80,84 Stable pitting corrosion generates an ECN signal that is characterized by large transients (typically larger than for metastable pitting). These can remain at a high value for a longer time than for metastable pitting (e.g., in the order of one hundred to several hundreds of seconds) before decreasing again.…”
Section: Visual Characterizationmentioning
confidence: 99%
“…[ 24 ] Localized corrosion is expected to have a low characteristic frequency and high characteristic charge. Chandrasatheesh et al [ 37 ] and Pujar et al [ 39 ] showed that localized corrosion of stainless steel associated with MIC corresponded to shot noise parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetry of the paired electrodes, possibly due to the variability of bacterial activity, biofilm, corrosion films, and aeration levels can result in macrocell polarization that will be reflected in these values. The standard deviation (σ) would ideally qualify the magnitude of the isolated noise transient events deviating from the mean, although larger values [37] Time domain, R n , shot noise 316 L stainless steel Iron-oxidizing bacteria, 1% NaCl Low f n and large q n corresponding to pitting corrosion -Homborg et al [38] Hilbert spectra of time domain Pujar et al [39] R n , shot noise UNS S31653 Stainless steel Slime-forming bacteria, 0.5 M NaCl Low f n and large q n corresponding to crevice -R n did not distinguish corrosion Zaveri et al [40] associated with wide noise bands could mask those phenomena. The localization index (LI) was defined as σ I /rms I and would ideally identify localized processes; however, interpretation of this value can be complicated due to the presence of bidirectional transients and the relative number of transient events in a time record.…”
mentioning
confidence: 99%
See 1 more Smart Citation